Green Synthesis of Silver Nanoparticles Using Pineapple Peel Extract as Bioreductant for Latent Fingerprint Visualization - Muhammad Rafif; Aldi Tobing; Tery Mardasela; Stefany Therisia; Riyan; Rosiana Pitri; Masriani Masriani (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2026)
This study aimed to identify the optimal conditions for synthesizing silver nanoparticles from pineapple peel (AC-AgNPs), characterize their physicochemical properties, and assess their efficacy as latent fingerprint detectors. The synthesis process involved varying the pH, extract concentration, AgNO₃ concentration, and heating duration. Characterization was conducted using UV-Vis spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, scanning electronic microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX), particle size analysis (PSA), and zeta potential analyses. Optimal conditions were established at pH 11, 0.08% extract concentration, 1 mM AgNO₃, and heating for 60 min. The synthesis of AgNPs was verified using UV–visible spectroscopy at a wavelength of 400-450 nm, as evidenced by a color change attributable to surface plasmon resonance. FTIR analysis revealed the involvement of –OH and C=O groups in the reduction and capping processes, while SEM-EDX results indicated slightly agglomerated particles with a silver content of 4.91% and an evenly dispersed particle morphology on the sample surface. PSA analysis determined an average particle size of 59.5 nm, and the Zeta Potential was -16.4 mV. The AC-AgNP powder effectively visualized latent fingerprints with clear and high-contrast ridge patterns on glass and paper surfaces without compromising the ridge structures. These findings suggest that AC-AgNPs have the potential to serve as environmentally friendly latent fingerprint detectors, in accordance with the principles of green chemistry.